Resistensi Tradisi Terhadap Modernitas - Abdul Jalil (Umbara, 2017)
This paper discussess  people understanding on the concept of tradition and modernity, in terms of material and immaterial tradition. This article has been inspired by Michael Rowland's idea on the ‘Inconsistent Temporalities in a Nation State’ published in Daniel Miller book ‘Worlds Apart Modernity Through The Prish of The Local.’ This paper aims to see the relationship and negotiation between the concept of tradition and modernity, as well examine the post  tradition phase. The method of analysis being used in this article is descriptive analysis. The results of the analysis suggests that the resistance of tradition to modernity had led to the emergence of postmodernity. Keywords: Resistance, Tradition, Modernity, Postmodernity